Pengaruh Teknik Tumpang Sari Tomat dan Kubis Serta Perlakuan Ekstrak Babadotan Terhadap Plutella Xylostella, L di Lapangan - Desi Sri Pasca Sari Sembiring (Universitas Serambi Mekkah, 2017)
The Purpose of this research was to know the influence of Intercropping Plant between tomatoes with cabbage and babadotan extract concentration ((Ageratum conyzoides, L )in the field. This research was done in Kabanjahe, Karo Highland which 1250 mdpl highest. The metode use Design random group (RAK) which is two factor, First Intercropping Farming techniq between tomatoes and cabbage (P) and second Extract Babadotan (Ageratum conyzoides,L). with the pattern of faktorial 3 x 3, it consist 9 combination of treatment and 27 plot trial. The result is: In Intercropping between tomatoes and cabbage the highest population P1 with average 9.00 and the highest attack population of larva at P1 with 54,12%, , in extract babadotan the highest population larva at B1 which is 73,90% the highest production, The highest production in P3 (tomat planting in all line) which is 44.70 ton/ha, Interaction between tomatoes and cabbage not significance influence to larva population Plutella xylostella L, Attack Intensity of Plutella xylostella L and plant production.